Postconditioning the Human Heart in Percutaneous Coronary Intervention - Xue, Feng (Clin Cardiol, 2010)
BACKGROUND: It has been proved in animal models that postconditioning (PC) could attenuate reperfusion injury. But there are not many clinical studies on the application of PC. HYPOTHESIS: Four cycles of 1‐minute balloon inflation and deflation, following initial balloon reperfusion in ST‐segment elevation myocardial infarction (MI) but before stenting, might improve clinical outcomes compared with primary percutaneous coronary intervention (PCI) alone. METHODS: Forty‐three patients diagnosed with acute MI were randomly assigned to 2 groups: the control group (n = 20) and the PC group (n = 23). Blood samples were obtained and assayed for creatine kinase MB (CK‐MB) and high‐sensitive C‐reactive protein. Electrocardiogram, echocardiography, and rest technetium Tc 99m‐sestamibi (99mTc‐MIBI) myocardial perfusion single‐photon emission computed tomography (SPECT) were performed. RESULTS: The control group presented with higher peak CK‐MB as compared with the PC group (351.9 ± 153.6 vs 247.7 ± 118.3 U/L, P = 0.028) as well as the area under the curve (AUC) of CK‐MB (8040 ± 3358 vs 5955 ± 2509, P = 0.04). After PCI, PC was associated with a lower level of hs‐CRP in comparison with the control group (5.5 ± 4.5 vs 9.5 ± 5.2 mg/L, P = 0.019). More patients in the PC group had complete ST‐segment resolution than did patients in the control group (82.6% vs 45.0%, P = 0.049). Left ventricle ejection fraction was better in the PC group than in the control group (0.57 ± 0.09 vs 0.47 ± 0.11, P = 0.002). Compared with the control group, PC greatly reduced infarct size, by 46% as measured by SPECT (13 ± 11.2% vs 24.2 ± 10.6%, P = 0.002). CONCLUSIONS: This study indicated that PC in emergent PCI was a valuable modification of primary PCI. Copyright © 2010 Wiley Periodicals, Inc.